Reducing time spent by junior doctors on call performing routine tasks at weekends. Issue 1 (27th August 2013) - Ibrahim, Wadah; Lin, Simeng
Abstract: At the Northern General Hospital, there are sixteen medical wards, spread over approximately half a mile. Weekend care for inpatients on these wards is provided by a team of four junior doctors, of different levels of training. We undertook a quality improvement project to reduce the amount of time junior doctors spent performing routine tasks at weekends. This may increase their available time for direct patient care. The study was performed over a period of nine weeks on two medical wards - Diabetes & Endocrine (W1) and Care of the Elderly Rehabilitation (W2). We monitored the bleeps received by the covering junior doctors during the weekend daytime shifts from the two study wards. We noted that a proportion of bleeps were routine tasks that could have been performed during weekday working hours. We also noted that W2 recorded fewer bleeps than W1 ward. This seemed to be because W2 batched junior doctors' jobs together. Firstly, we attempted to reduce the amount of routine work left undone each weekend. We provided a poster to remind Junior Doctors to complete such work during the week. Secondly, on W1 we replicated the job-batching system already in place on W2. A Doctors' Book was introduced in which nursing staff recorded the tasks that needed doing. This saved them from having to bleep the doctor repeatedly. The two changes resulted in a reduction in the number of bleeps generated by each ward and the number of visits required by the Junior Doctors to W1. Simple changes can reduce the amount of time junior doctors spend performing routine work at weekends. We implemented two such changes and achieved a reduction in the number of bleeps experienced by junior doctors and the number of times they had to return to one ward.